Organizers of inhibitory synapses come of age. (August 2017) - Krueger-Burg, Dilja; Papadopoulos, Theofilos; Brose, Nils
Highlights: The protein machinery at inhibitory synapses is more complex than anticipated. Many new synapse organizers have recently been identified. Major progress was made using proteomic approaches, particularly proximity labeling. A challenge now is to identify the exact functions of these proteins. New methodology will allow the identification of synapse-type specific proteomes. Abstract : While the postsynaptic density of excitatory synapses is known to encompass a highly complex molecular machinery, the equivalent organizational structure of inhibitory synapses has long remained largely undefined. In recent years, however, substantial progress has been made towards identifying the full complement of organizational proteins present at inhibitory synapses, including submembranous scaffolds, intracellular signaling proteins, transsynaptic adhesion proteins, and secreted factors. Here, we summarize these findings and discuss future challenges in assigning synapse-specific functions to the newly discovered catalog of proteins, an endeavor that will depend heavily on newly developed technologies such as proximity biotinylation. Further advances are made all the more essential by growing evidence that links inhibitory synapses to psychiatric and neurological disorders.